The Ifo industry growth accounting database - Oliver Roehn; Theo S. Eicher; Thomas Strobel (Center for Economic Studies and ifo Institute (CESifo), 2007)
In this paper we present a new database that allows deep industry-level growth accounting from 19912003. The database allows for the first complete analysis of the German industry performance drivers based on the contributions of 12 asset types in 52 different industries. The industry sources of productivity and output growth are crucial to the understanding of the transformation of the German economy from manufacturing to information technology and service industries. The database enables researchers to develop an adequate picture of the sources of growth using standard growth accounting techniques. We formally document the new data series and its origins, with special focus on the capital stock and capital service data.
Keywords: O4; O5; 330; Industrie; Verarbeitendes Gewerbe; Gesamtwirtschaftliches Anlagevermögen; Investition; Statistische Datenbank; Arbeitsproduktivität; Zeitreihenanalyse; Schätzung; Deutschland